ANALISA BIAYA PENINGKATAN JALAN NIAGA DAN SEKITAR SIMPANG PASIR SAMARINDA - KURNIA ROBBY, HAQIQI (KURVA S JURNAL MAHASISWA, 2014)
The estimated cost of the acquired cost calculation needs to complete an activity or employment in accordance with the requirements or contract . Estimates done by first studying the drawings and specifications . Based on the picture can be seen recana material needs, both the type and quality that will be used . Calculation type of material that must be priced , while the specification can be used as a basis for determining the quality of each type of material.The scope of the employment increase in the commercial and around the intersection of sand Samarinda East Kalimantan province has a formulation of the problem to be researched and dinalisa include the following : How can the analysis of volume calculation , equipment , labor costs and the overall cost for the work improvement of the commercial and around the intersection of sand.Data analysis technique or techniques of writing in this study are presented in a step -by-step analyzing unit price list of materials , analyzing unit price list tool , analyzing the price list unit labor costs , analyze recapitulation of the price , in order to get the budget plan are estimated for purposes of employment pavement planned.From the analysis of the prices obtained on the mobilization of approximately Rp 42.900.000,00 jobs , jobs pairs of stone with mortar around Rp 986.762,80 , job class B Aggregate Base about Rp 63.268,53 , concrete work structure of K - 250 around Rp 1.776.846 , 70 , work rebars U - 32 approximately Rp 21.874,44 , work joint sealent approximately Rp 16.831,78 , and the recapitulation or the overall price of all the jobs that exist around Rp 5.848.595.000,00.